Evaluation of tribological performance of hydrogenated DLC by surface texturing in the presence of palm BASED TMP ester at different temperatures - Varman, Mahendra; Ahmed, A.; Masjuki, Haji Hassan; Abul Kalam, M.; Zulkifli, Nurin Wahidah Mohd (2017)
Surface textured and DLC coated (hydrogenated amorphous carbon) samples were assessed for their coating performance at 40 ºC, 80 ºC and 125 ºC. As a result, textured a-C:H DLC demonstrated higher but stable coefficient of friction (COF) at high temperatures as compared to un-textured DLC samples. However, textured DLC samples showed higher wear resistance compared to un-textured DLC coating. The enhancement can be elucidated by the lower graphitization of textured DLC samples.